The relationship between the hygiene factors of herzberg theory and job satisfaction among non-executive employees in Sarawak Land Consolidation And Rehabilitation Authority (SALCRA) Kota Samarahan, Sarawak/ Claudia Jubik - Jubik, Claudia (2016)
The purpose of this study was to determine the top two hygiene factors that contribute to job satisfaction and the relationship between the hygiene factors and job satisfaction among non-executive employees in Sarawak Land Consolidation and Rehabilitation Authority (SALCRA) Kota Samarahan, Sarawak. There are three hygiene factors that investigated which are salary, supervision and work environment. All of the hygiene factors were tested in order to see which one are the main hygiene factors that contribute to job satisfaction and which hygiene factors that has a positive, high and significant relationship with job satisfaction. The total population was 120 non-executive employees and 92 was the sample size. Data collection was gathered by using a questionnaire. The result indicates that the main hygiene factors were work environment and supervision and there was a significant relationship between the hygiene factors (salary, supervision and work environment) and job satisfaction. The researcher recommends that the study should be done to other employees from another organization as well to see whether there are any similarities in the findings in studying the same field of research.